Sustainable Energy Harvesting System Utilizing Fluid-elastic Vibration of a Tube Array due to Ocean Flow - Ito, Tomohiro; Shintani, Atsuhiko; Nakagawa, Chihiro (European Journal of Sustainable Development, 2016)
Various types of sustainable energy harvesting systems have been developed and already in commercial use. After the accident in Fukushima nuclear power plant, these sustainable energy systems are becoming more important. But some of them such as wind turbine system deeply depend on the climate, and some types that utilize a turbine operating in the sea water have problems of corrosion or maintenance. Thus, we developed a new energy harvesting system that utilizes “Fluid-elastic Vibration of a Tube Array” due to ocean flow. This system does not depend on the climate change and the generator is placed above sea surface. In this paper, first, a theoretical study on the energy harvesting due to fluid-elastic vibration of a tube array was conducted in order to confirm the feasibility on the energy harvesting due to the proposed system. And secondly, a small scale test model was fabricated that utilized air flow instead of water flow, for convenience. Tests were conducted in the laboratory. The relationship between the flow rate and generated electric power were obtained for various tube array patterns. From both the theoretical and experimental studies, we confirmed that the proposed system could be one of the sustainable energy harvesting systems. In addition, the most efficient tube array as for energy harvesting was discussed. Key Words: Sustainability, Renewable energy, Energy harvesting system, Fluid-elastic vibration, Tube array, Ocean flow